Externalisation within the migration policy of the European Union - Balogh, Márton (Pécs journal of international and European law, 2026)
The externalisation of the migration policy within the European Union is a new approach of blocking migrants from the possibility of activating the safeguards of the European human rights. Despite having several case studies and mal-practices of the externalisation globally (e.g. the practice of the USA or Australia), the EU is uncovering its own approach – with its own flaws. This article offers to present the existing externalisation agreements between the EU and its partner countries, shows improper procedures and gives recommendations in order to be more humane towards persons arriving to Europe. The methodology of the paper is to analyse the text of the partnerships, then analyse their execution. Problematic practices and procedures are highlighted. In the recommendations part, the author attempts to give solutions to these issues.